ESENSI EVALUASI DALAM PERSPEKTIF FILSAFAH PENDIDIKAN ISLAM - Pulungan, Abdul Salam; Sholihat, Iis; Pulungan, Nur Amanah (STAI Bahriyatul Ulum Pandan, 2025)
As explained above, in the Qur'an, there are several terms that are always associated with the evaluation process, including reckoning, bala, and fatana. These three terms are often used in the sense of providing a treatment to carry out the process of measuring or evaluating human beings. From a philosophical rational perspective, Islamic education is tasked with forming al-Insan al-Kamil or the perfect human being. Therefore, evaluation of Islamic education should be directed at two dimensions, namely: the horizontal dialectical dimension and the vertical dimension of submission. The aim of educational evaluation is to determine the level of students' understanding of the subject matter, train courage and encourage students to recall the material that has been given. The purpose of educational evaluation is to measure and assess whether all educational programs and activities implemented have succeeded in realizing these programs and activities towards achieving the goals of Islamic education.